Risk Assessment of Radon Concentrations in Water of the Tapi River Nearby the Tapi Estuary of Bandon Bay, Muang District, Surat Thani Province - Titipornpun, Kanokkan; Komsan, Pattarawadee; Tohsuemae, Suaina; Sukgree, Narin (Science Essence Journal, 2021)
This work aimed to study the physical characteristics and measurements of radon activity concentrations in water. In addition, the annual effective doses for water consumption obtained from the Tapi river nearby the Tapi estuary of Bandon Bay, Muang district, Surat Thani province, were estimated. The 90 water samples were collected from 15 sampling sites of the Tapi river nearby the industrial factories and riverside communities. The radon activity concentrations in water were measured using the RAD7 electronic radon detector. The average values of electrical conductivity, background radiation dose, temperature, and pH were 0.33±0.32 S/m, 0.62±0.22 mSv/y, 30.41±0.99 °C, and 7.01±0.27, respectively. The radon activity concentrations were in the range of 0.06–0.97 Bq/L, with an average value of 0.37±0.18 Bq/L for all measured samples in the study area. These results indicated that all measured radon concentrations were lower than the alternative maximum contaminant level for raw water (148 Bq/L) recommended by the U.S. EPA. To estimate the annual effective doses for water intake in infants, children, adults, and the weighted estimate of consumption, the results were significantly lower than the proposed safe limit of 100 mSv/y recommended by the WHO. This work could be applied for further study on the correspondence of radon variation and submarine groundwater discharge into the Bandon Bay through the Tapi river. Moreover, the correlations of radon concentration in consumption water, soils, sediment in the river, and indoor radon in dwellings nearby the riverside area will be necessary to confirm the health safety due to radon.